Stochastic pausing at latent HIV-1 promoters generates transcriptional bursting - Katjana Tantale (Nature Portfolio, 2021)
The ability of HIV to alternate between acute and latent forms is thought to rely on a transcriptional feedback loop where polymerase pausing is released by the viral protein Tat. Here, the authors show that viral genome transcription can occur in a burst-like stochastic manner in the absence of Tat.